MENINGKATKAN PERKEMBANGAN MORAL ANAK DENGAN MENGGUNAKAN STRATEGI MORAL IMPLISIT - Titik Aliyahwati (AL-ASASIYYA: Journal Of Basic Education, 2019)
According to the moral foundation theory, moral judgments are based on five (or six) moral systems. The system is caring, justice, authority, loyalty, and purity with freedom as the potential of the six systems. For example, the caring system is sensitive to the signs of others who suffer and explains why we intuitively judge that hurting others is morally wrong. Bullying is included in the moral system of caring among children. Children will not do bullying towards their friends if they love and care for one another. The social process of bullying, where incidents often occur in the presence of parties involved indirectly, have been observed in the diversity of the school environment.